Large retroperitoneal hematoma in a patient with haemophilia B - Beedubailu, Ramya; Tubachi, Prashant (International Surgery Journal, 2021)
A spontaneous retroperitoneal hematoma is very rare and quite a challenging entity, more so when its presentation mimics other more common causes of acute abdomen, as in this interesting case. Here, patient presented with acute abdomen with polyarthralgia with flank ecchymosis (Grey Turner’s sign) with flank mass which lead us in the direction of acute pancreatitis. However, past history of recurrent bleeding episodes and positive family history along with blood investigations revealing an isolated prolongation of activated partial thromboplastin time tickled our brains with the differentials of coagulation disorders. Computed tomography showed large retroperitoneal hematoma. After initial resuscitation in the emergency room he was managed conservatively with fresh frozen plasma, cryoprecipitate and blood transfusions. On detailed evaluation, coagulation workup showed deficient coagulation factor IX levels leading us to the diagnosis of haemophilia B. Now, the patient is doing good on regular follow up.